Counselling for managers - MacLennan, Nigel 1961- (Gower, 1996)
This work takes a sympathetic and practical look at workplace counselling. The author, a qualified psychologist, makes counselling accessible as a performance management tool, and also explodes some of the myths with which the counselling profession surrounds itself.